Liquid biopsy: a new diagnostic method in clinical oncology - Bulgakova, O.V.; Kausbekova, A. Zh.; Bersimbaev, R.I. (KSU publ., 2018)
The goal of modern medicine is early diagnosis socially significant diseases that reduce the ability to work and affect on mortality in the population. Oncological diseases occupy second rank among the causes of deaths in Kazakhstan. At the same time, lung cancer is leading, the death rate from which in the Republic is 17.6 % of the total mortality from cancer. The cause of high mortality is the lack of effective diagnosis of lung cancer in the early stages of the disease. At the moment, clinical medicine does not have specific and highly sensitive oncomarkers suitable for using in screening studies of the population. Free-circulating nucleic acids, including mitochondrial DNA and microRNA, are stable in physiological fluids of the body, such as blood, serum, saliva, urine, etc. Moreover, the results of numerous studies have shown that the level of freecirculating nucleic acids can indicate pathological processes in the human body. This shows great prospects for the use of free-circulating nucleic acids as biomarkers for non-invasive diagnosis of cancer. In this review, we are presenting available data on the modern methods of non-invasive cancer detection, so called «liquid biopsy» based on free circulating nucleic acids.
Сұйық биопсия: клиникалық онкологияның жаңа диагностикалық əдісі
Жидкая биопсия: новый диагностический метод в клинической онкологии
Keywords: lung cancer; liquid biopsy; biomarkers; mitochondrial DNA; microRNA; free-circulating nucleic acids